Case report: a novel high-dose intravenous immunoglobulin preparation for the treatment of severe pemphigus vulgaris failing standard therapy - Wiedenmayer, Nadine; Hogrefe, Katharina; Mihalceanu, Silvia; Winkler, Julia K.; Enk, Alexander (The journal of dermatology, 2024)
Pemphigus vulgaris (PV) is a severe autoimmune bullous dermatosis that is characterized by autoantibodies against epidermal adhesion proteins causing painful mucosal and skin blistering. Standard treatments for PV include corticosteroids, steroid-sparing immunosuppressants, or intravenous monoclonal anti-CD20-antibody therapy. The European guidelines suggest high-dose intravenous immunoglobulin (IVIg) therapy as a promising approach for severe or treatment-resistant cases. We report on a 65-year-old woman with severe and recurrent disease who achieved long-term disease stabilization with IVIg treatment. Because of recurrent fatigue and headache, the patient was switched to an alternative IVIg preparation with a novel manufacturing process, thus ensuring high purity and better tolerability. We observed excellent efficacy, yet side effects remained largely unchanged. Further studies are necessary to evaluate the long-term efficacy and tolerability of this new IVIg preparation.
Gesehen am 26.02.2025